Could Nigella sativa Extract be a Promising Anticancer Agent? - Shabana, Mennatallah; Amer, Ahmed Abd El-Moniem (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Nigella sativa, commonly known as black seed, has a long history of traditional use in folk medicine. Recent scientific investigations have highlighted its significant therapeutic potential, particularly in cancer treatment. Thymoquinone, the primary bioactive compound in N. sativa, has demonstrated promising anticancer properties in numerous preclinical studies. This review comprehensively examines the current understanding of N. sativa's anticancer potential, focusing on the pharmacological actions of thymoquinone. We analyzed high-quality research articles from various databases to assess the efficacy of N. sativa and its constituents in cancer treatment. Furthermore, we explored the potential of N. sativa as an adjunct therapy within existing cancer treatment guidelines. Finally, we discuss the safety profile of N. sativa and propose future research directions to fully realize its therapeutic potential in cancer management.